“Cutting Them Down to Size”: Humbling and Protreptic in Plato’s Lysis - Anderson, Trevor; Comstock, Reid (Revista Archai, 2023)
This article examines the role that humbling plays in Socratic practice. Specifically, we consider how Socrates humbles his interlocutors in order to turn them towards the pursuit of philosophical friendship. We argue against a standard interpretation of humbling in the Lysis, which holds that Socrates humbles Lysis by exposing his own ignorance to him at 210d. Instead, we argue that the humbling occurs not when Lysis is (allegedly) made aware of his own ignorance, but at 222d near the end of the dialogue, when Lysis is made to think that he is not as good a friend as he thought he was. On this reading, Socrates humbles Lysis not by exposing to him his ignorance about theoretical matters but by suggesting to him that he may be not the sort of person he thought he was.